2009
DOI: 10.1126/science.1169499
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Evidence for Sharp Lithosphere-Asthenosphere Boundaries of Oceanic Plates

Abstract: The mobility of the lithosphere over a weaker asthenosphere constitutes the essential element of plate tectonics, and thus the understanding of the processes at the lithosphere-asthenosphere boundary (LAB) is fundamental to understand how our planet works. It is especially so for oceanic plates because their relatively simple creation and evolution should enable easy elucidation of the LAB. Data from borehole broadband ocean bottom seismometers show that the LAB beneath the Pacific and Philippine Sea plates is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
581
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(646 citation statements)
references
References 23 publications
45
581
1
1
Order By: Relevance
“…This mode of segregation was predicted with two-phase flow theory (1) and subsequently discovered in experiments (2,3). It has been proposed that meltenriched bands, if present in the mantle of Earth, would permit rapid extraction of melt (4), produce significant anisotropy in seismic wave propagation (5), and provide a mechanism for the seismic discontinuity that is, in some places, associated with the lithosphere-asthenosphere boundary (6). The emergence (7) and low angle (8) of melt-enriched bands under simple-shear deformation can be reproduced using two-phase flow theory with a non-Newtonian, isotropic viscosity.…”
mentioning
confidence: 82%
“…This mode of segregation was predicted with two-phase flow theory (1) and subsequently discovered in experiments (2,3). It has been proposed that meltenriched bands, if present in the mantle of Earth, would permit rapid extraction of melt (4), produce significant anisotropy in seismic wave propagation (5), and provide a mechanism for the seismic discontinuity that is, in some places, associated with the lithosphere-asthenosphere boundary (6). The emergence (7) and low angle (8) of melt-enriched bands under simple-shear deformation can be reproduced using two-phase flow theory with a non-Newtonian, isotropic viscosity.…”
mentioning
confidence: 82%
“…Recent laboratory (Hilairet et al, 2007) and seismological (Kawakatsu and Watada, 2007) studies suggested the existence of such layers (water-rich layer) on the upper surfaces of the subducting slab. Thin low-viscosity layers rich in melt have also been suggested on the lower boundary (lithosphere-asthenosphere boundary) (Kawakatsu et al, 2009). Such thin low-viscosity layers on the subducting slab surface may enable such a rapid adjustment.…”
Section: A Simple Two-dimensional Modelmentioning
confidence: 99%
“…This exercise can test whether there is a gradual increase in lithospheric thickness from C→D (Figure 11), as required by the proposed SCS spreading model. It has been demonstrated that the thickness of generated oceanic crust correlates with its formation age [93][94][95][96][97]. Therefore, one can calculate the formation age of oceanic crust using the estimated lithospheric thickness, which in turn can be used to estimate the initiation and termination ages of SCS spreading.…”
Section: Spreading History Of the South China Seamentioning
confidence: 99%